Efficacy of caerulomycin A in modulating macrophage polarization and cytokine response in a murine model of lipopolysaccharide-induced sepsis - Jun Zhang; Shiyue Tang (European Journal of Medical Research)
Abstract Background Sepsis is characterized by an excessive immune response. Modulation of the immune response, particularly macrophage polarization, may provide therapeutic benefit. The effects of Caerulomycin A (caeA), a known STAT1 phosphorylation inhibitor, on macrophage polarization and inflammatory markers were explored using a lipopolysaccharide (LPS)-induced sepsis mouse model. Methods A sepsis model was established in C57BL/6 mice induced by intraperitoneal injection of LPS, and the survival rate of mice was observed after treatment with different doses of caeA to determine the optimal therapeutic dose. For in-vitro assays using the RAW264.7 macrophage cell line, the concentration of caeA that was non-toxic to cell survival was screened using the MTT assay, followed by the analyses by qRT-PCR, ELISA, Western blot and flow cytometry for M1/M2 type macrophage markers (CD86, NOS2, CD206, ARG1) and inflammatory factors (IL-1β, IL-6, TNF-α, IL-4, and IL-10) expression. In addition, the phosphorylation levels of STAT1 and STAT6 in the JAK–STAT signaling pathway were detected. Results The results of in-vivo experiments showed that caeA treatment (20 mg/kg) significantly increased the survival of LPS-induced septic mice and decreased the expression of M1-type macrophage markers (CD86 and NOS2) and pro-inflammatory cytokines (IL-1β, IL-6, and TNF-α) while increasing the expression of M2-type markers (CD206 and ARG1) and anti-inflammatory cytokines (IL-4 and IL-10) expression. In in-vitro experiments, 20 μM caeA effectively inhibited LPS-induced polarization of M1-type macrophages without affecting the activity of RAW264.7 cells, and caeA significantly inhibited the phosphorylation of STAT1 yet enhanced the phosphorylation level of STAT6, as detected by Western blot. Conclusions CaeA effectively modulates macrophage polarization and attenuates the inflammatory response in septic mice, possibly by affecting the JAK–STAT signaling pathway. These findings support further exploration of the potential of caeA as a therapeutic agent for sepsis.